Fluoxetine inhibits the metabolism of tolterodine—pharmacokinetic implications and proposed clinical relevance - Brynne, N (Blackwell Science Inc, 1999)
AIMS: To investigate the change in disposition of tolterodine during coadministration of the potent cytochrome P450 2D6 (CYP2D6) inhibitor fluoxetine. METHODS: Thirteen patients received tolterodine l-tartrate 2 mg twice daily for 2.5 days, followed by fluoxetine 20 mg once daily for 3 weeks and then concomitant administration for an additional 2.5 days. They were characterized as extensive metabolizers (EM1 with one functional CYP2D6 gene, EM2 with two functional genes) or poor metabolizers (PM). RESULTS: Nine patients, three EM2 and four EM1 and two PM, completed the trial. Following tolterodine administration, the area under the serum concentration–time curve (AUC) of tolterodine was 4.4-times and 30-times higher among EM1 and PM, respectively, compared with EM2. The AUC of the 5-hydroxymethyl metabolite (5-HM) was not quantifiable in PM. Fluoxetine significantly decreased (P < 0.002) the oral clearance of tolterodine by 93% in EM2 and by 80% in EM1. The AUC of 5-HM increased in EM2 and decreased in EM1. However, the exposure to the active moiety (unbound tolterodine +5-HM) was not significantly increased in the two phenotypes. The subdivision of the EM group showed a 2.1-fold increase in active moiety in EM2 but the exposure was still similar to EM1 compared with before the interaction. CONCLUSIONS: The study suggests a difference in the pharmacokinetics of tolterodine and its 5-hydroxymethyl metabolite depending on the number of functional CYP2D6 genes. Fluoxetine significantly inhibited the hydroxylation of tolterodine. Despite the effect on the pharmacokinetics of tolterodine in extensive metabolizers, the clinical effect is expected to be within normal variation.